2017
DOI: 10.4103/ijccm.ijccm_478_16
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6: An Early Predictive Marker for Severity of Acute Pancreatitis

Abstract: Background and Aims:Interleukin (IL)-6, IL-8, IL-10, and C-reactive protein (CRP) have been evaluated for predicting outcomes of acute pancreatitis. However, there is considerable variation in their performance among different studies. We evaluate their accuracy in predicting progression to severe pancreatitis.Materials and Methods:Serum IL-6, IL-8, IL-10, and CRP levels were measured within 24 h of admission in forty patients of clinically predicted severe acute pancreatitis (SAP). Persistent organ failure (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…IL6 is an important inflammatory mediator of the acute-phase response that has been experimentally associated with distant organ complications [20]. In addition, in the clinical setting, it is considered a reliable early marker for predicting the severity of acute pancreatitis [21,22]. We found that both the prophylactic and therapeutic use of PEG35 was able to significantly abrogate the up-regulated levels of systemic IL6 following ANP induction.…”
Section: Discussionmentioning
confidence: 87%
“…IL6 is an important inflammatory mediator of the acute-phase response that has been experimentally associated with distant organ complications [20]. In addition, in the clinical setting, it is considered a reliable early marker for predicting the severity of acute pancreatitis [21,22]. We found that both the prophylactic and therapeutic use of PEG35 was able to significantly abrogate the up-regulated levels of systemic IL6 following ANP induction.…”
Section: Discussionmentioning
confidence: 87%
“…[13][14][15] Biochemical markers, such as IL-6, IL-8, CRP, and IL-10, in addition to scoring systems, such as the Ranson criteria, the Baltazar score, and the APACHE II score have been used to estimate prognosis. [16] The present study was designed to use biochemical tests that are easily accessible and inexpensive to physicians regardless of location in order to predict the severity and prognosis of AP. RDW is a low-cost and reliable whole blood analyzer parameter showing the distribution of erythrocyte volume and can be measured easily and simply.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are critical mediators of acute inflammatory responses in pancreatitis. Several cytokines have been implicated in the caerulein model of pancreatitis, and some studies have shown that IL‐1β, TNF‐α, IL‐6, and IL‐10 in particular play critical roles in the pathogenesis of both animal and human pancreatitis . As predicted, the pancreatic IL‐1β, TNF‐α, and IL‐6, but not IL‐10, mRNA levels were elevated in the caerulein‐induced models.…”
Section: Resultsmentioning
confidence: 63%
“…Cytokines play a major role in the development of inflammation and necrosis during both the experimental mouse AP model and human AP. Experimentally, blocking the proinflammatory cytokine cascade, even after the initiation of pancreatitis, results in a dramatic decrease in the severity of AP . IL‐1β, TNF‐α, and IL‐6 have been shown to be implicated in the promotion of inflammation and acinar necrosis in different models of AP.…”
Section: Discussionmentioning
confidence: 99%